Effects of physical exercise programs on cognitive function in Parkinson's disease patients: A systematic review of randomized controlled trials of the last 10 years. - Franciele Cascaes da Silva; Rodrigo da Rosa Iop; Laiana Cândido de Oliveira; Alice Mathea Boll; José Gustavo Souza de Alvarenga; Paulo José Barbosa Gutierres Filho; Lídia Mara Aguiar Bezerra de Melo; André Junqueira Xavier; Rudney da Silva (PLoS ONE, 2018)
Background Given the relative importance of cognitive impairment, there was considerable interest in identifying the cognitive profile of PD patients, in order to ensure specific and appropriate therapeutic interventions. Purpose To determine the effects of physical exercise programs on cognitive function in PD patients, compared with the control group. Data sources Medline, Cochrane, Scopus, PEDro and Web of Science (last searched in September 2016). Study selection Randomized clinical trials examining the effects of physical exercise programs and cognitive function in PD patients. Nine studies fulfilled the selection criteria and were included in this review. Data extraction Characteristics of the publication, characteristics of the participants, test used for cognitive screening, cognitive domain assessed, tools used to assess cognitive function, characteristics of the experimental intervention, characteristics of the control group, mean results and standard deviation of function cognitive. The PEDro score was used to evaluate methodological quality. Data synthesis Most eligible studies showed good methodological quality based on the PEDro scale. Studies have shown that adapted tango for PD patients, cognitive training combined with motor training, and treadmill training promote the preservation or improvement of cognitive function in PD patients. Limitations The diversity of cognitive tests used to assess cognitive function and the high heterogeneity identified between the physical exercise programs. Conclusions Physical exercise programs promote positive and significant effects on global cognitive function, processing speed, sustained attention and mental flexibility in PD patients, at a mild to moderate stage for patients with a 6-year clinical diagnosis of PD. However, treadmill training performed 3 times a week for about 60 minutes and for a period of 24 weeks produced larger improvements in cognition.